If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 4x = 0 Reorder the terms: 4x + 6y = 0 Solving 4x + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 4x + 6y + -6y = 0 + -6y Combine like terms: 6y + -6y = 0 4x + 0 = 0 + -6y 4x = 0 + -6y Remove the zero: 4x = -6y Divide each side by '4'. x = -1.5y Simplifying x = -1.5y
| 48=2v+12 | | 7+3x=0.5(14+6x) | | z/7-9=3 | | t-17=20 | | 2x+5+2x+3x= | | 4(x-1)=-5(x+3)+32 | | -60x+32=Qx+p | | 5x+(2x-2)-(4x-3)= | | 3w+15=18 | | 3xy+9xy-5xy= | | 3(x-3)+2(x+2)=40 | | Y=4x^3-3x^2 | | F(x)=x^3-4x^2-5x | | 7(p+2)=-4(-4p-8) | | -2(5x+1)=-3-3x | | 3(5n-5)=-90 | | 9c=5(101)-160 | | z-10=28 | | -8(4x-3)+6x=-158 | | -8(3x+1)+5x=87 | | 91=7(-5a-2) | | 2n/3=11 | | -6(3x+5)=60 | | (9*9)-(8+4)= | | -6k+15=-5k+2k | | -10-(-63)= | | -117+4x=12x+107 | | (-5)+x=32 | | 900t-10t^2=0 | | 4(5-4x)-3x=96 | | 2(5-2x)=1.2(3x-5) | | 4(5-4x)-3x=97 |